Pengaruh Alokasi Aset, Pemilihan Saham dan Tingkat Risiko Terhadap Reksadana Saham Syariah di Indonesia Tahun 2015-2019 - Maziyah Mazza Basya; Betty Silfia Ayu Utami (Al-Muraqabah: Journal of Management and Sharia Business, 2021)
The purpose of this study was to determine the effect of asset allocation, stock selection, and the level of risk on Islamic mutual funds in Indonesia. The research method used is multiple linear regression. The data used in this study are secondary data such as the NAB report for Islamic equity mutual funds in Indonesia from 2007-to 2011. The results showed that stock selection had a positive and significant effect on Islamic equity mutual funds in Indonesia, while asset allocation and risk had a negative effect on Islamic equity mutual funds in Indonesia.